Clinical phase I data of the first orally available anti‐aβ‐prionic drug PRI‐002 that reverses behavioral and cognitive deficits, and decelerates neurodegeneration in AD animal models: Human/Human trials: Other. (7th December 2020) - Willbold, Dieter; Kutzsche, Janine; Willuweit, Antje; Windisch, Manfred; Jürgens, Dagmar
Abstract: Background: More and more data suggest that the toxic protein assemblies of Aβ and TAU behave prion like. The drug candidate PRI‐002 has been developed to directly disassemble and destroy toxic Aβ oligomer prions. The anti‐prionic compound PRI‐002 (alias "RD2") is BBB penetrable and has demonstrated target engagement in vitro and in vivo . Treatments in three different transgenic mouse models in three different laboratories yielded improved cognition and deceleration of neurodegeneration. Oral treatment of old‐aged transgenic AD mice with full‐blown pathology reversed cognitive and behavioral deficits to levels of healthy wild‐type littermates. We wanted to demonstrate safety and tolerability of PRI‐002 in healthy volunteers up to doses that are much higher than the expected therapeutic dose. Method: We carried out a single (4 to 320 mg PRI‐002) and a multiple ascending dose (160 and 320 mg PRI‐002/volunteer) phase I clinical trial in 63 healthy volunteers. Result: No drug‐related adverse events (AE) have been observed in the SAD study. The few possibly drug‐related AEs in the MAD study were equally distributed across groups. Already in the SAD, PRI‐002 plasma levels were reached (AUC0‐24 104 ng h/mL) that were measured in the highest dosed animals of the successful preclinical PoC studies. Conclusion: Daily administered oral doses of PRI‐002 up to 320 mg/subject/day for 28 days have been proven to be safe. PoC studies in humans for anti‐prionic compounds may be based on shorter treatment durations and do not necessarily have to be life‐long.